Light Stress Responses by the Eelgrass, Zostera marina (L) - Bertelli, Chiara M.; Unsworth, Richard K. F. (Frontiers in Environmental Science, 2018)
Zostera marina is the dominant seagrass species in the Northern Hemisphere where it grows in sheltered bays and estuaries. As a consequence of its distribution its conservation is commonly threatened by poor coastal water quality. The high minimum light requirements of seagrasses results in water quality degradation (high turbidity and eutrophication) being a significant risk. Bioindicators of light stress can be used to interpret seagrass responses to light limitation and therefore act as sentinels for conservation management. However, there exists limited experimental inter-comparison of the effectiveness of multiple individual bioindicator responses. Meta-analysis suggests that rhizome sugars, shoot C:N, shoot growth and number of leaves per shoot provide the most consistent response variables to increasing light limitation in seagrass, but this premise remains largely untested at the plant level as a direct comparison of multiple bioindicators. The present study aimed to test the morphological, physiological and photo-physiological bioindicator responses of Z. marina to light stress applied within controlled laboratory conditions. These bioindicators were used to assign minimum light thresholds. Growth rate and photophysiological parameters (alpha, Ek and ETRmax) were rapidly (1st week) and drastically affected by low light shade treatments (20.12 µmol photons m-2s-1 and lower). After three weeks at low light, significant reductions in maximum leaf length and leaf width were observed. Principal Component Analysis identified leaf length, shoot growth, shoot surface area, ETRmax, Ek and alpha as having the strongest responses to reduced light. Shoot growth, ETRmax, Ek and alpha were found to provide the best early warning of light limitation after 5-8 days. These results provide evidence for bioindicators of light stress in Z. marina and highlights the importance of understanding these responses for the successful management and conservation of this species.